Germination of jack bean Canavalia ensiformis (L.) DC. and its impact on nutrient and anti-nutrient composition - Agustia, Friska Citra (Rynnye Lyan Resources, 2023)
The nutrient and anti-nutrient composition of jack bean sprouts were investigated as a local alternative protein source. This study used six germination time treatments of 12, 24, 36, 48, 60, and 72 hrs. The morphology of the sprouts was studied using a descriptive approach, while the nutrition and anti-nutritional components were analyzed by analysis of variance. The results indicate that germination time significantly increased protein solubility and amino acid concentration, whereas HCN, phytic acid, trypsin inhibitors, and tannin decreased with germination time. Sprouts germinated for 60 and 72 hrs had radicle lengths of about 8 to 9 cm, respectively, and were categorized at a safe cyanide level for consumption according to the WHO. These sprouts are rich in hydrophobic amino acids, such as phenylalanine, isoleucine, leucine, and valine, which are potential bioactive peptides. Â© 2023 The Authors.